2007
DOI: 10.1063/1.2720759
|View full text |Cite
|
Sign up to set email alerts
|

Buckling modes of elastic thin films on elastic substrates

Abstract: Two buckling modes have been observed in thin films: buckle-delamination and wrinkling. This Letter identifies the conditions for selecting the favored buckling modes for elastic films on elastic substrates. Transition from one buckling mode to another is predicted as the stiffness ratio between the substrate and the film or the interfacial defect size varies. The theoretical results are demonstrated experimentally by observing the coexistence of both buckling modes and mode transition in one film-substrate sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(135 citation statements)
references
References 20 publications
(17 reference statements)
2
133
0
Order By: Relevance
“…2. As the constraints at the delamination edges relax from the clamped ones (zero displacement and rotation) to the hinged ones (zero displacement and bending moment), the buckling load reaches the lower limit of ∆ 2 c−c /4 [8]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2. As the constraints at the delamination edges relax from the clamped ones (zero displacement and rotation) to the hinged ones (zero displacement and bending moment), the buckling load reaches the lower limit of ∆ 2 c−c /4 [8]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(13) implicitly assumes that only delamination buckling occurs and there is no wrinkling. However, Mei et al [8] showed that when E * s /E * f is very small (less than 10 −3 ) with relatively small b/t ratio (b/t = 5, 10, and 20, respectively), which corresponds to the B < 2 scenario, the wrinkling load/stress is smaller than that of delamination buckling. Therefore, wrinkling occurs before the delamination buckling, and the Yu-Hutchinson model becomes inapplicable [8], which implies that the lower limit is unphysical.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially wrinkling mechanisms can be used to create tunable patterns [1], to fabricate functional surfaces [2], to design flexible electronics [3] and/or to measure the mechanical properties of materials [4]. It refers to periodic or chaotic surface undulations appearing on an originally flat surface.…”
Section: Introductionmentioning
confidence: 99%